Kemampuan Memukul Bola Dengan Pemukul Tanpa Modifikasi Dan Pemukul Modifikasi Dalam Permainan Bola Bakar Siswa Kelas V SD Negeri 38 Kota Bengkulu: Ability to hit the ball with an unmodified bat and a modified bat in the Bola bakar game for the fifth grade students of SD Negeri 38 Bengkulu City - Desfian Kurniawan; Andes Permadi; Oddie Barnanda Rizky (SPORT GYMNASTICS : Jurnal Ilmiah Pendidikan Jasmani, 2023)
ABSTRACT This study aims to determine the description of the ability to hit the ball of students in the game of bola bakar by using an unmodified bat and a modified bat in the fifth grade students of SD Negeri 38 Bengkulu City. The samples used in this study were VB class students, totaling 27 male students, and 15 female students with a total of 42 students. This type of research is quantitative descriptive using survey method because it only describes the condition of the research object in a limited way. The results of quantitative descriptive analysis with percentages in the ball hitting ability test in this study can be concluded as follows: The ability to hit using a bat without modification with a mean value of 9.21 is categorized as "Medium", and hitting ability using a modified bat with a mean value of 11.90 is categorized as 'High'. . It can be concluded that the ability to hit a bola bakar with a modified bat is much better than that of a bola bakar bat without modification. The advantage of a modified bat with a wider cross section makes it easier for students to hit the ball when hitting the ball. From the results of research that has been carried out in class V SD Negeri 38 Bengkulu City, it can be seen that the ability to hit a bola bakar with a modified bat can better assist students in hitting the ball in the bola bakar game. Keywords : bola bakar game, fifth grade students, hitting ability.